Knowledge-Based Approach for the Structural Assessment of Monumental Buildings: Application to Case Studies - Caprili, Silvia; Puncello, Irene (Frontiers in Built Environment, 2019)
Historical buildings are characterised by high level of complexity due to a long realization process often resulting in an overall lack of information and in a structural behaviour that is more like to ‘structural aggregates’ rather than ‘single building’. The assessment of the static safety and seismic vulnerability then requires a multidisciplinary and multi-level approach including a deep and accurate preliminary knowledge phase before performing structural analyses. In the present paper, a consolidated knowledge-based procedure is presented and applied to four case studies in Italy. Interest is focused on the knowledge phase, joining critical-historical analysis to in-situ architectural, geometrical, structural, material and geotechnical aspects. The knowledge phase proves to be fundamental to understand the structural behaviour of cultural heritage, with special attention to the determination and analysis of local mechanisms and vulnerability elements and allowing to validate and give reason to numerical results.